Impacto da taxa de escalada da tarifa de energia elétrica para diferentes classes de consumo e regiões do Brasil - Pinheiro, Andrey Dantas (Universidade Federal Rural do Semi-Árido, 2020)
With the emergence of globalization that has made the lifestyle of the population increasingly technological and connected, through electronic devices and consumer goods increasingly electronic, it is necessary for each country to ensure greater energy security due to most of the fundamental processes of a country depend on electricity for its operation. With this, the human being has increasingly discovered new ways of harnessing energy, such as renewable energies that have gained prominence in recent years through their efficient forms of generation. With the increase in consumption increasing due to this new standard of increasingly electronic equipment comes the concern to verify the availability of this energy in addition to the cost that it can generate for the government and the population. The tariff modalities and consumption classes are defined by ANEEL, which is the regulatory agency in Brazil, responsible for regulating the energy concessionaires of each state and ensuring that these standards are met. Thus, the work consists of studying rates such as the IPCA, which is the government's official rate for measuring inflation in Brazil, and the SELIC rate, which is the basic interest rate used by the government, to be able to verify the real escalation rates of energy (e ̂) in brazil, for each region and each class of consumption, through energy consumption data (MWh) and the revenue from the supply of this electric energy that are made available by ANEEL from 2003 to 2019 and with these data we use an analysis method in which it will be possible to arrive at a current value (PV) and with these values we can verify which region and class of consumption in Brazil has the best profitability to apply investments in energy efficiency projects such as generation distributed, which appears as an alternative from a renewable source and the possible replacement of motors already in use by new high-performance motors in the industrial sector.
Keywords: Consumo de energia; Eficiência energética; ANEEL; Taxa de escalada; Rentabilidade; Energy consumption; Energy efficiency; Climbing rate; Profitability; ENGENHARIAS::ENGENHARIA ELETRICA